Development of The An-Najah Mobile Learning Application to Improve Students’ Arabic Reading Skills - Pratama, Muhamad Ibnu Setiawan; Sumiarni, Nanin; Saefuloh, Hasan (Arabiyat : Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2025)
The integration of technology in educational settings has revolutionized conventional teaching approaches, particularly in language instruction. This research investigates the development and efficacy of the An-Najah mobile learning application designed to enhance reading competencies among students at Madrasah Aliyah Negeri (MAN) 2 Cirebon. Employing a research and development methodology, this study utilized the ADDIE framework (Analysis, Design, Development, Implementation, Evaluation) to construct and validate the educational technology intervention. The results of the study show that Arabic language learning at MAN 2 Cirebon city is still based on traditional media and faces various challenges in teaching reading skills; The an-Najah app developed has a very good feasibility rate based on the assessment of media experts (96%) and content experts (83%) with an average feasibility of 90%; and effectiveness testing through pre-test and post-test showed a significant increase from an average score of 55.4 to 90.8, showing an increase of 63.9%. However, the challenge of teaching Arabic reading skills still requires adaptive educational media innovation.